Social science research for undergraduate survey, case Study and action research /c Mohd Ghani Awang ; edited by Fadzida Ismail - Mohd. Ghani Awang (Publisher Universiti Malaysia Pahang, 2014)
This book is published in order to help undergraduates in doing their research especially in social science research